P Peran Guru dalam Mengembangkan Kemampuan Membaca pada Peserta didik di Madrasah Ibtidaiyah Darul Da'wah Wal Irsyad (DDI) Ujuna Kota Palu - Nurleli; aniati; Andi Nurfaizah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Beginning reading, the reader does not yet have actual reading skills, but is still in the learning stage to acquire reading skills or abilities. The fact was found that in class III students at Madrasah Ibtidaiyah Darul Da'wah Wal Irsyad (DDI) Ujuna, Palu City, there were several students who were still reading with a halt, couldn't put words together, and some couldn't read. This thesis is entitled